GOVERNANCE NETWORK ON AVIATION SAFETY: A SYSTEMATIC LITERATURE REVIEW - Oke Hendra; Rini Sadiatmi; Zulham Hidayat (Journal of Airport Engineering Technology (JAET), 2023)
The governance network serves as a crucial conceptual framework to be applied within the context of air transportation policy, particularly concerning aviation safety. This study aims to conduct a systematic literature review of prior research focusing on governance networks in the aviation safety sector and to elaborate on the existing knowledge landscape, identify prevailing research gaps, and formulate pertinent implications for future investigations. The review relies on a systematic literature review comprising 67 publications from the Scopus database. The review process adheres to the PRISMA method, wherein data from each article are categorized and documented in worksheet format. This approach facilitates systematic data grouping and subsequent descriptive and thematic analysis. The result from the review reveals a significant body of prior research about governance networks within the aviation context, predominantly in Europe and the United States. Research on networks and governance in the aviation sector has been underway since 2004. However, research explicitly applying the concept of governance network within the aviation context remains somewhat limited. Over 18 years, only 19 relevant articles have been identified. Furthermore, applying network governance concepts in aviation safety contexts is an underexplored area, with only ten articles focusing on this aspect. These findings underscore substantial opportunities for further research in the future.